Evaluating the pentapharmacological potency of otamixaban against lung cancer CDK2, transferase, oxidoreductase and signalling proteins - Hanadi M. Baeissa; Tahani Bakhsh; Afnan Mohammed Shakoori; Ghadir Sindi; Randa Mohammed Zaki; Mohammad Azhar Kamal; Hadeel A. Alsufyani; Alaa Hamed Habib; Arwa Ishaq A. Khayyat; Misbahuddin Rafeeq; Deeba Shamim Jairajpuri (PLoS ONE, 2025)
Lung cancer remains the leading cause of cancer-related mortality worldwide. With approximately 2.2 million new cases and 1.8 million deaths annually, it contributes to 18% of all cancer fatalities. The high mortality rate, limited accessibility to affordable treatments, and the emergence of drug resistance necessitated the development of novel therapeutic strategies. In this study, we employed an HTVS, SP and XP-based molecular docking and MM/GBSA calculations to identify a potential multitargeted drug candidate from the DrugBank library against five key (Penta) lung cancer-associated proteins, including CDK2 (1AQ1), Transferase(1JWH, 1K3A), Oxidoreductase (4XZL) and Signalling (2DVJ) enzymes that led to the identification of Otamixaban, exhibiting favourable docking and MM/GBSA scores ranging from −11.841 to −6.52, and −69.96 to −45.22 kcal/mol. Molecular Interaction Fingerprints analysis was performed to gain deeper insights into its binding interactions that reveal key residues with high interaction frequencies, including 12VAL, 8LEU, 7PHE, 6LYS, 5ASP, 5GLN, and 5GLU. Pharmacokinetic evaluations confirmed drug-likeness, and its ADMET properties were consistent with standard drug approval benchmarks, QM computations using DFT further reinforced the stability and reactivity of the identified compound. The thermodynamic role of water molecules in ligand binding was assessed through 5 ns WaterMap analysis, supporting the hypothesis that Otamixaban effectively interacts with the binding pockets of multiple target proteins. Further, a 100-ns MD simulation was conducted to ensure the stability and efficacy of the drug candidate under physiological conditions in an explicit TIP3P water environment. The results demonstrated minimal structural deviations and fluctuations, with strong intermolecular interactions persisting throughout the simulation. Further evaluation of 1000 simulation frames from trajectories provided comprehensive insights into the total complex energy and binding free energy via MM/GBSA calculations, reinforcing the potential of Otamixaban as a robust multitargeted drug candidate. Despite these promising computational findings, experimental validation through in vitro and in vivo studies is crucial to confirm its therapeutic efficacy and clinical viability.